Self-efficacy and digital anxiety and their influence on virtual educational performance: a diagnostic study in a sample of students from a private university in Lima – Peru - Iraola Arroyo, Juan Alonso (2023)
Digital self-efficacy is the personal confidence to use technology tools efficiently. Digital self-efficacy reduces anxiety and increases student per-formance. For these reasons, the present research proposes to analyze the levels of digital self-efficacy and anxiety, as well as their influence on virtual performance in university students in Peru. 116 students participated, 105 females (90.5%) and1 1 males (9.5%) between 17 and50 years of age (Mean = 26.78, SD = 7.02). The results showed that the students have optimal levels of digital self-efficacy and virtual performance. Nevertheless, they were hesitant to feel digital anxiety. Then, digital self-efficacy was related to virtual performance. Finally, the con-cept “digital native” is discussed because the youngest students did not achieve optimal levels of digital self-efficacy, neither with low levels of digital anxiety.